The Role of Aconitase in the Regulation of Metabolism and Sporulation in Bacillus subtilis. - Pechter, Kieran. (2017)
Abstract: Previously, it was shown that an aconitase (citB) null mutation results in a vast over-accumulation of citrate in the culture supernatant of growing Bacillus subtilis cells, a phenotype that causes secondary effects, including the hyper-expression of the citB promoter. The first chapter of this thesis, in part, reveals the mechanism of this hyper- expression: CcpC, which acts as a repressor in the absence of citrate, was shown to act through a binding site at the -66 position on the citB promoter to activate expression of aconitase in high levels of citrate. In addition, the mechanism behind the accumulation of citrate in a citB null was elucidated. Two different aconitase point mutants were created: an enzymatically dead aconitase (C450S; citB2), and a mutant aconitase defective in RNA binding (R741E; citB7). The citB2 mutant (Enz-) was a glutamate auxotroph while the citB7 mutant (RNA-) was a glutamate prototroph; unexpectedly, the citB7 strain accumulated citrate in the culture supernatant. Both citB2 and citB7 cells exhibited overexpression of the citB promoter and high levels of aconitase protein. These strains exhibited higher levels of citrate synthase protein and activity in cell extracts compared to wild-type. The same is true for a citB null mutant strain. Indeed, the major citrate synthase gene (citZ) was overexpressed in citB null cells independent of CcpC. Wild-type Acn bound to an in vitro transcribed citZ leader RNA by filter binding assay, but the mutant proteins (C450S, R741E) did not. In addition, the R741E mutant was ~4- fold less enzymatically active than the wild-type aconitase. The second chapter of the thesis describes an analysis of the aconitase-dependent regulation of gerE gene expression, a previously described target of aconitase. A delay in the appearance of GerE protein in the citB5 strain was demonstrated, and a sequence in the 3' UTR of the gerE message was necessary for proper GerE protein accumulation. The third chapter of the thesis describes a new purification scheme for aconitase. Wild-type and mutant (C450S, R741E) forms of aconitase were purified from B. subtilis without overexpression using a four-step purification scheme.; Thesis (Ph.D.)--Tufts University, 2011.; Submitted to the Dept. of Molecular Microbiology.; Advisor: Abraham Sonenshein.; Committee: Carol Kumamoto, Joan Mecsas, Brian Schaffhausen, and Susan Fisher.; Keyword: Microbiology.